Pengaruh Pelaksanaan Baby gym terhadap Perkembangan Bayi - Syuhrotut Taufiqoh (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Objective: Infancy is a critical period that requires stimulation to stimulate growth and development—one of the efforts to stimulate the baby’s development. This study aims to determine the effect of implementing a baby gym on baby development in the Jagir Health Center, Surabaya, working area.Methods: This research was conducted in March 2020. This study uses a quasi-experimental approach with